Barriers to the Institutionalization of University Extension: Experience of the Universidad Nacional, Costa Rica - Monge-Hernández, Carmen (2021)
The current challenges demand that the statutory social mission of public universities be strengthened, where the university extension stands out as key. The incoherence of academic management in many universities restricts this integration due to conceptual, methodological and operational gaps present in the extension process. The present article shows the results of a qualitative research, Rica, through the study of case, carried out in Escuela de Planificación y Promoción Social of the Universidad Nacional de Costa Rica, with the objective of exploring the university barriers that disturb the contribution of higher education to the fourth United Nations Sustainable Development Goal: to achieve quality, inclusive, and equitable education with expanded opportunities for more people.